Makna Takwa dalam Tafsir Al-Mishbah (Hamalatul Qur'an : Jurnal Ilmu Ilmu Alqur'an, 2024)
Many of the Islamic community have not understood the word piety in accordance with what the Qur'an wants to teach, so that is the reason for this writing. The selection of Tafsir Al-Misbah by Muhammad Quraisy Shihab because it is the work of modern/contemporary mufasir in Indonesia. In addition, this book uses the Maudhū'i method or the Thematic method. data sources in this study are divided into two, namely primary data sources and secondary data sources, the primary data source in this study is the book Tafsir Al-Misbah written by Muhammad Quraisy Syihab, while the secondary data sources in this study are books, articles, thesis journals, then books or other works that are relevant to the theme being studied. The implementation of the meaning of piety in everyday life, that true piety becomes the driving force to invite good and prevent evil (nahi mungkar), If everyone has the virtue of taqwa, they will definitely be the best people.